Coefficient inequalities for a subclass of bounded turning functions associated with a domain bounded by an epicycloid - Nithiyanandham, E. K.; Sruthakeerthi, B. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.5We consider a subclass of bounded turning functions $\mathcal{BT}_{n-1,\mathcal{L}}$ associated with a domain bounded by an epicycloid with $n-1$ cusps. Our primary task is to examine some coefficient inequalities, as well as the second and third Hankel determinants for the newly defined class.